Pengembangan UMKM Tempe Nugget Desa Seberang Sungai - Adinda Septi Aulia; Delpi Lestari; Elentika Elentika; Ilham Khalib; Meili Safitri; M Aziz Noval Agusta; Nadila Feranti; Tazkiyatul Hidayah; Zelpi Ayuni; Zuhroh Mahdalena (STIKes Ibnu Sina Ajibarang, 2023)
Tempeh is a food made from soybeans fermented using white Rhizopus spp mushrooms, tempeh can be further processed into processed food that can be developed by the community into processed food that is causal and has high selling value through the Community Partnership Program based on the application of TTG. The purpose of implementing this activity is to provide new innovations for local food raw materials and also to improve the economy of housewives in villages across the river. The target of this activity is community empowerment in developing products, training entrepreneurial spirit and increasing product sales. The output of this activity is food diversification in the form of healthy and nutritious food products to support immunity such as tempeh nuggets, temped chocolate and tempeh sticks. The implementation methods of this Community Partnership Program include: 1) Planning and socialization of activity programs, 2) Preparation and provision of activity tools and materials, 3) Training on the use of Autoclave tools, 4) Training on diversification of tempeh processed products, 5) Strengthening partner business management, 6) Monitoring and evaluation of PKM. This activity stimulates SME groups to increase tempeh production in the culinary business of healthy food snacks processed from tempeh